Answer:
![x = (1 + √((-219)) )/(22) , \space x = (1 - √((-219)) )/(22)](https://img.qammunity.org/2020/formulas/mathematics/high-school/pbxhyo3gkcazk0x5tav3am18n5eufijssu.png)
Explanation:
f(x)=11x^2+x+5 is the given equation,
now comparing it with the standard equation
, we get
Here, a = 11, b = 1 and c = 5
Now by QUADRATIC FORMULA
x =
![\frac{-b \pm \sqrt{b^(2) - 4ac} }{2a}](https://img.qammunity.org/2020/formulas/mathematics/high-school/bdk9rgkqtwco4nsf3zbm4h5p8qyoim911o.png)
Now,
![b^(2) - 4ac = 1^(2) - 4 (11) (5) = 1 - 220 = -219](https://img.qammunity.org/2020/formulas/mathematics/high-school/ocgl46i4ssaublzpin7q6g92w4lsnz5f9o.png)
Now as discriminant D < 0, then the roots are imaginary and distinct.
So, roots are
![x = (-1 + √((-219)) )/(22) , \space x = (-1 - √((-219)) )/(22)](https://img.qammunity.org/2020/formulas/mathematics/high-school/fq7dgdml8z7qcr2jrogvj9l67fe9bm54xd.png)
These are the two roots of the given equation.